Adobe Photoshop CS5 Digital Classroom - Smith, Jennifer; AGI Creative Team (Indianapolis, IN, 2010)
The Adobe Photoshop CS5 Digital Classroom helps you to understand the capabilities of Photoshop and get the most out of your software so you can get up-and-running right away. You can work through all the lessons in this book, or complete only specific lessons. Each lesson includes detailed, step-by-step instructions, along with lesson files, useful background information, and video tutorials.
Keywords: Adobe Photoshop; Computer graphics; Photography Digital Technique